Validity and reliability of a self-acceptance scale for youth with physical disabilities - Abdul Wahat, Nor Wahiza; Ahrari, Seyedali; D’Silva, Jeffrey Lawrence; Mohamed, Noraini; Hassan, Siti Aishah (Universiti Putra Malaysia, 2021)
Youth with disabilities generally struggle to earn a good livelihood as they journey through life. Disability acceptance is acceptance of impairment or loss of worth or acceptance of failure in the sense of disability. It involves changes in one’s values, placing less importance on one’s physical disability and more on one’s remaining assets or abilities. To develop the Self-Acceptance Scale for youth with physical disabilities (SAS-PD), this study adopted the sequential exploratory design. The scale was administered on 247 persons with physical disabilities. Following the compilation and analysis of qualitative data, a quantitative study was conducted. The Exploratory Factor Analysis (EFA) identified six factors, viz. social stigma, enlargement, and asset value, containment of disability effect, family support, and body acceptance that were represented by fifty items in a questionnaire that covered the attributes examined in the scale. The assessment of the level of self-acceptance by youth with disabilities using the SAS-PD may be a valuable intervention for transition programs. Going forward, the scale could also be used to build the profile of people with physical disabilities before they begin participating in any face to face or virtual training program. The assessment of youth with disability self-acceptance level enables their parents and teachers to be aware of their mental state and lead to more strategic planning for the teaching-learning approach.